Polarizing plate, manufacturing method therefor, and image display device having the same

By integrating a urea-based compound-containing layer in the polarizing plate, the issue of transmittance reduction in high-temperature environments for image display devices with interlayer filling structures is addressed, ensuring improved durability and display characteristics.

JP2025061711AInactive Publication Date: 2025-04-11SUMITOMO CHEM CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2025004843
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-05-15
Filing Date
2025-01-14
Publication Date
2025-04-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Polarizing plates used in image display devices with interlayer filling structures experience significant reductions in transmittance when exposed to high-temperature environments, leading to durability issues.

Method used

Incorporating a urea-based compound-containing layer, such as an adhesive layer with urea, urea derivatives, thiourea, or thiourea derivatives, on at least one surface of the polarizing element, which is then bonded to an image display cell and a transparent member like a touch panel or front plate.

Benefits of technology

This configuration effectively prevents decreases in transmittance and maintains high-temperature durability, even in image display devices with interlayer filling structures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061711000001
    Figure 2025061711000001
  • Figure 2025061711000002
    Figure 2025061711000002
  • Figure 2025061711000003
    Figure 2025061711000003
Patent Text Reader

Abstract

To provide a polarizing plate which exhibits less reduction in transmittance in high-temperature environments and superior durability even when used in an image display device with an interlayer filling configuration, a manufacturing method therefor, and an image display device with improved display characteristic and durability in the high-temperature environments.SOLUTION: A polarizing plate is provided, comprising: a polyvinyl alcohol-based resin polarizing element with iodine absorbed and aligned therein; a urea-based compound-containing layer formed on at least one surface of the polarizing element, the urea-based compound-containing layer containing at least one selected from urea, urea derivatives, thiourea, and derivatives of thiourea; and a transparent protective film.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polarizing plate and a manufacturing method thereof, and further to an image display device in which one surface of the polarizing plate is bonded to an image display cell and the other surface is bonded to a transparent member such as a touch panel or a front panel. [Background technology]

[0002] Liquid crystal display devices (LCDs) are widely used not only in LCD televisions, but also in personal computers, mobile devices such as mobile phones, and in-vehicle applications such as car navigation systems. Typically, a liquid crystal display device has a liquid crystal panel member in which polarizing plates are attached to both sides of a liquid crystal cell with an adhesive, and displays images by controlling the light from a backlight member with the liquid crystal panel member. In recent years, organic EL display devices, like liquid crystal display devices, have also come to be widely used in televisions, mobile devices such as mobile phones, and in-vehicle devices such as car navigation systems. In organic EL display devices, a circular polarizer (a laminate including a polarizing element and a λ / 4 plate; hereinafter, sometimes simply referred to as a polarizer) may be disposed on the viewing side surface of the image display panel in order to prevent external light from being reflected by the metal electrode (cathode) and being viewed as a mirror surface.

[0003] As mentioned above, polarizing plates are increasingly being installed in vehicles as components of liquid crystal display devices and organic electroluminescence display devices. Polarizing plates used in vehicle-mounted image display devices are more often exposed to high-temperature environments than those used in other mobile applications such as televisions and mobile phones, and are therefore required to have small changes in properties at high temperatures (high-temperature durability). On the other hand, for the purpose of preventing damage to the image display panel due to impact from the outer surface, a configuration in which a front plate such as a transparent resin plate or a glass plate (also referred to as a "window layer" or the like) is provided on the viewing side further than the polarizing plate of the image display panel is becoming more common. Also, in display devices equipped with a touch panel, a configuration in which a touch panel is provided on the viewing side further than the polarizing plate of the image display panel and a front plate is provided on the viewing side further than the touch panel is widely adopted.

[0004] In such a configuration, if there is an air layer between the image display panel and a transparent member such as a front plate or a touch panel, the light reflection at the interface of the air layer causes the reflection of external light, which tends to reduce the visibility of the screen. For this reason, there is a growing trend to adopt a configuration in which the space between the polarizing plate and the front transparent member arranged on the viewing side surface of the image display panel is filled with a material having a refractive index close to that of these materials (hereinafter, sometimes referred to as an "interlayer filling configuration"). As the interlayer filling material, a pressure sensitive adhesive or a UV curing adhesive is used for the purpose of suppressing the decrease in visibility due to the reflection at the interface and bonding and fixing each member (see, for example, Patent Document 1).

[0005] The above-mentioned interlayer filling structure is being widely adopted for mobile applications such as mobile phones that are often used outdoors. In addition, due to the increasing demand for visibility in recent years, the adoption of a structure in which a front plate is placed on the surface of an image display panel and an adhesive layer or the like is used to fill the gap between the panel and the front plate is being considered for in-vehicle applications such as car navigation devices. However, when such a configuration is adopted, it has been reported that the results of a heat durability test (e.g., at 95°C for 200 hours) show a significant decrease in transmittance in the center of the polarizing plate surface, whereas the polarizing plate alone does not show a significant decrease in transmittance even after 1,000 hours at 95°C. Based on these results, it has also been reported that the significant decrease in transmittance of the polarizing plate in a high-temperature environment is a problem specific to the case where an image display device employing an interlayer filling configuration in which one surface of the polarizing plate is bonded to an image display cell and the other surface is bonded to a transparent member such as a touch panel or front panel is exposed to a high-temperature environment (Patent Document 2).

[0006] In addition, in the above-mentioned Patent Document 2, a polarizing plate in which the transmittance is significantly reduced due to the interlayer filling structure is Spectroscopic measurement at 1100cm -1 near (derived from the C-C bond) and 1500 cm -1 Since there is a peak near the -C=C bond, it is a polyene structure (-C=C). n-, and it is presumed that this is the result of the polyvinyl alcohol that constitutes the polarizing element being dehydrated to form a polyenen (Patent Document 2, paragraph

[0012] ). In addition, the inventors performed Raman spectroscopy on samples that had been subjected to high-temperature durability tests with an interlayer-filled structure, and found that the 1100 cm -1 Near and 1500 cm -1 It is observed that the sum of the peak areas in the vicinity increases.

[0007] As a solution to this problem, Patent Document 2 proposes a method of suppressing the decrease in transmittance by keeping the moisture content per unit area of ​​the polarizing plate below a specified amount and keeping the saturated water absorption amount of the transparent protective film adjacent to the polarizing element below a specified amount. However, further testing by the inventors revealed that the effect of the above solutions in suppressing deterioration was not necessarily sufficient, and furthermore, it was found that in order to reduce the moisture in the polarizing plate during panel production, it becomes necessary to heat the polarizing plate or the panel to which the polarizing plate is attached, resulting in a new problem of reducing panel productivity. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] Japanese Patent Application Publication No. 11-174417 [Patent Document 2] JP 2014-102353 A Summary of the Invention [Problem to be solved by the invention]

[0009] In view of the above circumstances, the object of the present invention, that is, the problem that the present invention is to solve, is to provide a polarizing plate and a manufacturing method thereof that exhibits little decrease in transmittance and excellent durability even when used in an image display device with an interlayer filling configuration. Another object of the present invention is to provide an image display device having improved display characteristics and durability in a high-temperature environment. [Means for solving the problem]

[0010] As a result of extensive research, the present inventors have found that in a configuration in which a transparent protective film is provided via an adhesive layer on at least one surface of a polarizing element formed by adsorbing and aligning iodine in a polyvinyl alcohol-based resin layer, by containing at least one type selected from urea, urea derivatives, thiourea and thiourea derivatives (hereinafter, urea, urea derivatives, thiourea and thiourea derivatives are also simply referred to as "urea-based compounds") in the adhesive layer, it is possible to suppress a decrease in transmittance in a high-temperature environment in an interlayer filling configuration in which one surface of the polarizing plate is bonded to an image display cell and the other surface is bonded to a transparent member such as a touch panel or a front panel.

[0011] As a result of further investigation, it was found that by laminating a layer containing at least one type of urea-based compound (hereinafter also referred to as a "urea-based compound-containing layer") on at least one surface of the above polarizing element, even if the layer is other than an adhesive layer, it is possible to suppress the decrease in transmittance in a high-temperature environment in an interlayer filling configuration, as in the first invention.

[0012] Furthermore, it has been found that, among the urea-based compounds of the present invention, in devices employing an interlayer filling configuration, urea derivatives or thiourea derivatives exhibit excellent performance not only in terms of the effect of suppressing the decrease in transmittance in a high-temperature environment, but also in terms of the effect of suppressing the decrease in polarization degree (preventing cross loss) in a high-temperature environment. Based on these newly discovered facts, the present inventors have completed the present invention.

[0013] The problem to be solved by the present invention can be solved by the following means. (1) A polyvinyl alcohol-based resin polarizing element having iodine adsorbed and oriented therein; formed on at least one surface of the polarizing element A urea-based compound-containing layer containing at least one selected from urea, urea derivatives, thiourea, and thiourea derivatives; and Transparent Protective Film A polarizing plate comprising: (2) The polarizing plate according to (1), wherein the urea compound-containing layer is an adhesive layer and the transparent protective film is attached via the adhesive layer. (3) The polarizing plate according to (2), wherein the adhesive layer further contains a polyvinyl alcohol-based resin. (4) The polarizing plate according to (3), characterized in that the total content of the urea-based compounds contained in the adhesive layer is 1 part by weight or more and 400 parts by weight or less per 100 parts by weight of the polyvinyl alcohol-based resin.

[0014] (5) The polarizing plate according to any one of (1) to (4), wherein the urea compound is a urea derivative and / or a thiourea derivative. (6) The polarizing plate according to any one of (2) to (5), wherein the adhesive layer has a thickness of 0.01 to 7 μm. (7) The polarizing plate according to (1), wherein the urea compound-containing layer is a resin layer other than an adhesive layer. (8) The polarizing plate according to any one of (1) to (7), which is used in an image display device having an interlayer packing structure.

[0015] (9) A method for producing a polarizing plate having a transparent protective film attached to at least one surface of a polarizing element, comprising the steps of: At least one surface of a polarizing element made of a stretched polyvinyl alcohol-based resin film on which iodine has been adsorbed and oriented is provided. Polyvinyl alcohol resin and forming an adhesive layer using an adhesive composition containing at least one selected from urea, urea derivatives, thiourea, and thiourea derivatives; A method for producing a polarizing plate, comprising the step of laminating a transparent protective film via the adhesive layer simultaneously with or after the step of forming the adhesive layer.

[0016] (10) An image display panel in which the polarizing plate according to any one of (1) to (9) is attached to a viewing side surface of an image display cell via a pressure-sensitive adhesive layer; and an image display device comprising: a transparent member attached to a viewing-side polarizing plate surface of the image display panel via an adhesive layer; (11) The image display device according to (10), wherein the transparent member is a glass plate or a transparent resin plate. (12) The image display device according to (10), wherein the transparent member is a touch panel. Effect of the Invention

[0017] The present invention makes it possible to provide a polarizing plate and a manufacturing method thereof that exhibit little decrease in transmittance in high-temperature environments and have excellent high-temperature durability, even when used in an image display device with an interlayer filling configuration; and further, by using the polarizing plate of the present invention, it is possible to provide a display device in which decrease in transmittance in high-temperature environments is suppressed. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] In one embodiment of the present invention, iodine is adsorbed and aligned in a polyvinyl alcohol-based resin layer. In the structure in which a transparent protective film is provided via an adhesive layer on at least one surface of the polarizing element, the adhesive layer contains at least one member selected from the group consisting of urea, urea derivatives, thiourea and thiourea derivatives.

[0019] The technical elements constituting the present invention will be described below, but the elements other than the urea compound-containing layer are common to other embodiments (embodiments in which the urea compound-containing layer is a layer other than the adhesive layer). [Polarizing element] As the polarizing element of the present invention in which iodine is adsorbed and aligned in the polyvinyl alcohol (hereinafter also referred to as PVA)-based resin layer, a well-known polarizing element can be used. Such a polarizing element is generally formed by using a PVA-based resin film, dyeing the PVA-based resin film with iodine, and uniaxially stretching the PVA-based resin film.

[0020] As described above, the PVA resin is generally obtained by saponifying a polyvinyl acetate resin. The degree of saponification is about 85 mol% or more, preferably about 90 mol% or more, more preferably about 99 mol% to 100 mol%. Examples of the polyvinyl acetate resin include polyvinyl acetate, which is a homopolymer of vinyl acetate, as well as copolymers of vinyl acetate and other monomers copolymerizable therewith, such as ethylene-vinyl acetate copolymers. Examples of the other copolymerizable monomers include unsaturated carboxylic acids, olefins, vinyl ethers, and unsaturated sulfonic acids. The degree of polymerization of the PVA resin is 1000 to 10000, preferably 1500 to 5000. The PVA resin may be modified, and may be, for example, polyvinyl formal, polyvinyl acetal, polyvinyl butyral, or the like, modified with aldehydes.

[0021] The method for producing the polarizing element is not particularly limited, but typically includes a method in which a polyvinyl alcohol-based resin film wound in advance in a roll is sent out and stretched, dyed, crosslinked, etc., or a method including a step of preparing a laminate of a polyvinyl alcohol-based resin and a resin substrate for stretching and stretching the laminate. Either of these methods can be used in the present invention. Methods for producing these polarizing elements are described in paragraphs

[0109] to

[0128] of JP2014-48497A, and these methods can be used in the present invention. The thickness of the polarizing element of the present invention is preferably 3 to 35 μm, more preferably 4 to 30 μm, and even more preferably 5 to 25 μm.

[0022] [Urea-based compound-containing layer] The polarizing plate of the present invention has a urea-based compound-containing layer containing at least one compound selected from urea, urea derivatives, thiourea and thiourea derivatives, formed on at least one surface of a polyvinyl alcohol-based resin polarizing element having iodine adsorbed and oriented thereon. In the present invention, the urea compound-containing layer does not necessarily have to be an adhesive layer, but from the viewpoint of productivity, it is preferable that the adhesive layer contains a urea compound. The adhesive layer is formed from the following adhesive. The structure of the urea compound-containing layer other than the adhesive layer will be described later.

[0023] [glue] Any suitable adhesive can be used as the adhesive for bonding the protective film to the polarizing element. Specifically, the adhesive can be a water-based adhesive, a solvent-based adhesive, or an active energy ray curable adhesive, but a water-based adhesive is preferred. When the adhesive layer is a layer containing a urea-based compound, the adhesive contains at least one selected from urea, urea derivatives, thiourea, and thiourea derivatives. The thickness of the adhesive when applied can be set to any appropriate value. For example, it is set so that an adhesive layer having a desired thickness is obtained after curing or heating (drying). The thickness of the adhesive layer is preferably 0.01 μm to 7 μm, and more preferably 0.01 μm to 5 μm. The thickness is preferably 0.01 μm to 2 μm, more preferably 0.01 μm to 1 μm, and most preferably 0.01 μm to 1 μm.

[0024] (Water-based adhesive) Any suitable aqueous adhesive may be used as the aqueous adhesive. Among them, an aqueous adhesive containing a PVA resin (PVA adhesive) is preferably used. The average polymerization degree of the PVA resin contained in the aqueous adhesive is preferably about 100 to 5500, more preferably 1000 to 4500, from the viewpoint of adhesiveness. The average saponification degree is preferably about 85 mol% to 100 mol%, more preferably 90 mol% to 100 mol%, from the viewpoint of adhesiveness.

[0025] The PVA resin contained in the water-based adhesive preferably contains an acetoacetyl group, because it has excellent adhesion between the PVA resin layer and the protective film and excellent durability. The acetoacetyl group-containing PVA resin can be obtained, for example, by reacting a PVA resin with diketene by any method. The acetoacetyl group modification degree of the acetoacetyl group-containing PVA resin is typically 0.1 mol% or more, and preferably about 0.1 mol% to 20 mol%. The resin concentration of the above-mentioned water-based adhesive is preferably 0.1% by weight to 15% by weight, and more preferably 0.5% by weight to 10% by weight.

[0026] (Crosslinking agent, solvent) The water-soluble PVA adhesive preferably used in the present invention may contain a crosslinking agent as necessary in addition to the above-mentioned PVA resin and urea compound. Known crosslinking agents can be used as the crosslinking agent. Examples of the crosslinking agent include water-soluble epoxy compounds, dialdehydes, and isocyanates.

[0027] When the PVA-based resin is an acetoacetyl group-containing PVA-based resin, the crosslinking agent is preferably any one of glyoxal, glyoxylate, and methylolmelamine, more preferably any one of glyoxal and glyoxylate, and particularly preferably glyoxal.

[0028] The water-soluble PVA adhesive of the present invention may contain an organic solvent. In this case, the organic solvent is preferably an alcohol because of its miscibility with water, and among alcohols, methanol or ethanol is more preferable. In the present invention, some of the urea derivatives have low solubility in water but sufficient solubility in alcohol. In that case, one of the preferred embodiments is to dissolve the urea derivative in alcohol to prepare an alcohol solution of the urea derivative, and then add the alcohol solution of the urea derivative to the aqueous PVA solution to prepare the adhesive.

[0029] (Active energy ray curing adhesive) As the active energy ray curable adhesive, any suitable adhesive can be used as long as it is an adhesive that can be cured by irradiation with active energy rays. Examples of the active energy ray curable adhesive include ultraviolet ray curable adhesives and electron beam curable adhesives. Specific examples of the curing type of the active energy ray curable adhesive include radical curable type, cationic curable type, anionic curable type, and combinations thereof (for example, a hybrid of radical curable type and cationic curable type).

[0030] The active energy ray-curable adhesive may, for example, be an adhesive containing, as a curing component, a compound (for example, a monomer and / or oligomer) having a radical polymerizable group such as a (meth)acrylate group or a (meth)acrylamide group. Specific examples of the above-mentioned active energy ray-curable adhesive and a method for curing the same are described in, for example, JP-A-2012-144690.

[0031] [Urea compounds] In the present invention, the adhesive layer contains at least one selected from urea, urea derivatives, thiourea and thiourea derivatives. As a method for incorporating a urea-based compound in the adhesive layer, it is preferable to incorporate the urea-based compound in the above-mentioned adhesive. Note that, in the process of forming the adhesive layer from the adhesive through a drying process, etc., it does not matter if a part of the urea-based compound migrates from the adhesive layer to the polarizing element, etc. Urea compounds include water-soluble and poorly water-soluble urea compounds, and both types can be used in the present invention. When a poorly water-soluble urea compound is used in a water-soluble adhesive, it is preferable to devise a dispersion method so that an increase in haze does not occur after the adhesive layer is formed.

[0032] When the adhesive is an aqueous adhesive containing a PVA-based resin, the amount of the urea-based compound added is preferably 0.1 to 400 parts by weight, more preferably 1 to 200 parts by weight, and even more preferably 3 to 100 parts by weight, per 100 parts by weight of the PVA-based resin.

[0033] (Urea or urea derivatives) In the present invention, the urea derivative means a compound having a molecular structure in which a part of urea is substituted with a substituent. The urea derivative is preferably a compound in which at least one of the four hydrogen atoms of the urea molecule is substituted with a substituent. In this case, the substituent is not particularly limited, but is preferably a substituent consisting of carbon atoms, hydrogen atoms and oxygen atoms.

[0034] Specific examples of urea derivatives include mono-substituted ureas such as methylurea, ethylurea, propylurea, butylurea, isobutylurea, N-octadecylurea, 2-hydroxyethylurea, hydroxyurea, acetylurea, allylurea, 2-propynylurea, cyclohexylurea, phenylurea, 3-hydroxyphenylurea, (4-methoxyphenyl)urea, benzylurea, benzoylurea, o-tolylurea, and p-tolylurea. Disubstituted ureas include 1,1-dimethylurea, 1,3-dimethylurea, 1,1-diethylurea, 1,3-diethylurea, 1,3-bis(hydroxymethyl)urea, 1,3-tert-butylurea, 1,3-dicyclohexylurea, 1,3-diphenylurea, 1,3-bis(4-methoxyphenyl)urea, 1-acetyl-3-methylurea, 2-imidazolidinone (ethylene urea), and tetrahydro-2-pyrimidinone (propylene urea). Examples of 4-substituted ureas include tetramethylurea, 1,1,3,3-tetraethylurea, 1,1,3,3-tetrabutylurea, 1,3-dimethoxy-1,3-dimethylurea, 1,3-dimethyl-2-imidazolidinone, and 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidinone.

[0035] (Thiourea or thiourea derivatives) In the present invention, the thiourea derivative means a compound having a molecular structure in which a part of thiourea is substituted with a substituent. The thiourea derivative is preferably a compound in which at least one of the four hydrogen atoms of the thiourea molecule is substituted with a substituent. In this case, the substituent is not particularly limited, but is preferably a substituent consisting of carbon atoms, hydrogen atoms and oxygen atoms.

[0036] Specific examples of thiourea derivatives include monosubstituted thioureas such as N-methylthiourea, ethylthiourea, propylthiourea, isopropylthiourea, 1-butylthiourea, cyclohexylthiourea, N-acetylthiourea, N-allylthiourea, and (2-methoxyethyl)thiourea. thiourea, N-phenylthiourea, (4-methoxyphenyl)thiourea, N-(2-methoxyphenyl)thiourea, N-(1-naphthyl)thiourea, (2-pyridyl)thiourea, o-tolylthiourea, and p-tolylthiourea. Examples of the disubstituted thiourea include 1,1-dimethylthiourea, 1,3-dimethylthiourea, 1,1-diethylthiourea, 1,3-diethylthiourea, 1,3-dibutylthiourea, 1,3-diisopropylthiourea, 1,3-dicyclohexylthiourea, N,N-diphenylthiourea, N,N'-diphenylthiourea, 1,3-di(o-tolyl)thiourea, 1,3-di(p-tolyl)thiourea, 1-benzyl-3-phenylthiourea, 1-methyl-3-phenylthiourea, N-allyl-N'-(2-hydroxyethyl)thiourea, and ethylenethiourea. An example of the 3-substituted thiourea is trimethylthiourea, and an example of the 4-substituted thiourea is tetramethylthiourea or 1,1,3,3-tetraethylthiourea.

[0037] Among the above compounds, urea derivatives or thiourea derivatives are preferred, and urea derivatives are more preferred, in that when used in an image display device with interlayer packing, there is little decrease in transmittance and polarization degree in a high-temperature environment. Among the urea derivatives, mono- or di-substituted ureas are preferred, and mono-substituted ureas are more preferred. Di-substituted ureas include 1,1-substituted ureas and 1,3-substituted ureas, and 1,3-substituted ureas are more preferred.

[0038] [Transparent protective film] The transparent protective film used in the present invention (hereinafter, simply referred to as "protective film") is attached to at least one side of a polarizing element via the urea compound-containing adhesive layer of the present invention. This transparent protective film is attached to one or both sides of the polarizing element, but it is more preferable that it is attached to both sides. In a configuration in which protective films are bonded to both sides of a polarizing element via adhesive layers, only one of the adhesive layers on both sides of the polarizing element may be the urea-based compound-containing adhesive layer of the present invention, but it is more preferable that both adhesive layers on both sides are the urea-based compound-containing adhesive layer of the present invention.

[0039] In recent years, in order to meet the demand for thinner polarizing plates, polarizing plates having a protective film on only one side of the polarizing element have been developed. Even in this configuration, it is preferable to laminate the protective film via the urea compound-containing adhesive layer of the present invention. One possible method for producing a polarizing plate having a protective film on only one side of a polarizing element is to first produce a polarizing plate in which protective films are attached to both sides via an adhesive layer, and then peel off one of the protective films. When such a production method is used, it is acceptable for only one of the adhesive layers to be the adhesive layer of the present invention, but it is more preferable that the urea-based compound-containing adhesive layer of the present invention is used on both sides of the polarizing element. When the urea compound-containing adhesive layer of the present invention is used on only one side of a polarizing element, it is preferable that the adhesive layer on the film side that is not to be peeled off is the urea compound-containing adhesive layer of the present invention.

[0040] The protective film may also have other optical functions, and may have a laminated structure in which other layers are further laminated. In this case, the thickness of the protective film is preferably thin from the viewpoint of optical properties, but if it is too thin, the strength decreases and the processability becomes poor. The appropriate thickness is 5 to 100 μm, preferably 10 to 80 μm, and more preferably 15 to 70 μm.

[0041] The protective film may be a cellulose acylate resin film, a polycarbonate resin film, a cycloolefin resin film such as norbornene, a (meth)acrylic polymer film, or a polyester resin film such as polyethylene terephthalate. A film such as a film can be used. In the case of a configuration having protective films on both sides of a polarizing element, when bonding is performed using a water-based adhesive such as a PVA-based adhesive, it is preferable that the protective film on at least one side be either a cellulose acylate film or a (meth)acrylic polymer film from the standpoint of moisture permeability, and of these, a cellulose acylate film is preferred.

[0042] At least one of the protective films may have a retardation function for the purpose of viewing angle compensation or the like. In this case, the film itself may have a retardation function, a separate retardation layer may be provided, or a combination of both may be used. Although the configuration in which the film having phase difference function is directly attached to the polarizing element via an adhesive has been described, it may also be attached via a pressure-sensitive adhesive or adhesive via another protective film that is attached to the polarizing element.

[0043] [Image display device configuration] The polarizing plate of the present invention, i.e., a polarizing plate having a transparent protective film attached to at least one side of a polarizing element via a urea-based compound-containing adhesive layer, is used in various image display devices such as liquid crystal display devices, organic EL display devices, etc. In particular, the polarizing plate of the present invention is suitably used in an image display device having an interlayer filling configuration in which a transparent member such as a front plate or a touch panel is disposed on the viewing side of the image display device and the image display panel and the transparent member are attached to each other via a pressure-sensitive adhesive layer or the like.

[0044] (Image display cell) Examples of the image display cell include a liquid crystal cell and an organic EL cell. The liquid crystal cell may be a reflective liquid crystal cell that uses external light, a transmissive liquid crystal cell that uses light from a light source such as a backlight, or a semi-transmissive semi-reflective liquid crystal cell that uses both external light and light from a light source. When the liquid crystal cell uses light from a light source, the image display device (liquid crystal display device) has a polarizing plate disposed on the opposite side to the viewing side of the image display cell (liquid crystal cell), and further has a light source disposed thereon. The polarizing plate on the light source side and the liquid crystal cell are preferably attached to each other via an appropriate adhesive layer. The liquid crystal cell can be driven in any type, such as VA mode, IPS mode, TN mode, STN mode, or bend alignment (π type).

[0045] As the organic EL cell, a light-emitting body (organic electroluminescence light-emitting body) is preferably formed by sequentially laminating a transparent electrode, an organic light-emitting layer, and a metal electrode on a transparent substrate. The organic light-emitting layer is a laminate of various organic thin films, and various layer configurations can be adopted, such as a laminate of a hole injection layer made of a triphenylamine derivative or the like and a light-emitting layer made of a fluorescent organic solid such as anthracene, a laminate of these light-emitting layers and an electron injection layer made of a perylene derivative or the like, or a laminate of a hole injection layer, a light-emitting layer, and an electron injection layer.

[0046] (Laminating image display cell and polarizing plate) A pressure-sensitive adhesive layer (pressure-sensitive adhesive sheet) is preferably used for bonding the image display cell and the polarizing plate. Among them, a method of bonding a polarizing plate with a pressure-sensitive adhesive layer, in which a pressure-sensitive adhesive layer is attached to one side of the polarizing plate, to the image display cell is preferred from the viewpoint of workability and the like. The pressure-sensitive adhesive layer can be attached to the polarizing plate by a suitable method. For example, a pressure-sensitive adhesive solution of about 10 to 40% by weight is prepared by dissolving or dispersing a base polymer or a composition thereof in a solvent consisting of a single or mixture of suitable solvents such as toluene and ethyl acetate, and the solution is directly attached to the polarizing plate by a suitable spreading method such as a casting method or a coating method, or a method of forming a pressure-sensitive adhesive layer on a separator in accordance with the above and transferring the solution to the polarizing plate.

[0047] (Adhesive layer) The adhesive layer is described in paragraphs

[0103] to

[0143] of JP2018-025765A, and these adhesives can be used in the present invention.

[0048] (Front transparent part) Examples of the front transparent member disposed on the viewing side of the image display cell include a front plate (window layer) and a touch panel. A transparent plate having appropriate mechanical strength and thickness is used as the front plate. Such a transparent plate may be, for example, a transparent resin plate such as an acrylic resin or a polycarbonate resin, or a glass plate. A functional layer such as an anti-reflection layer may be laminated on the viewing side of the transparent plate. In addition, when the transparent plate is a transparent resin plate, a hard coat layer may be laminated to increase physical strength, or a low moisture permeable layer may be laminated to reduce moisture permeability. As the touch panel, various touch panels such as resistive, capacitive, optical, and ultrasonic touch panels, as well as glass or transparent resin plates having a touch sensor function, are used. When a capacitive touch panel is used as the front transparent member, it is preferable that a front plate made of glass or transparent resin plate is provided on the viewing side further than the touch panel.

[0049] (Bonding the polarizing plate and the front transparent material) A pressure sensitive adhesive or a UV curable adhesive is preferably used to bond the polarizing plate and the front transparent member. When a pressure sensitive adhesive is used, the pressure sensitive adhesive can be applied in a suitable manner. As a specific application method, for example, the application method of the pressure sensitive adhesive layer used in bonding the image display cell and the polarizing plate described above can be mentioned.

[0050] When using a UV-curing adhesive, a method is preferably used in which a dam material is provided around the periphery of the image display panel to prevent the adhesive solution from spreading before curing, the front transparent member is placed on the dam material, and the adhesive solution is then poured in. After the adhesive solution is poured in, alignment and degassing are performed as necessary, and then UV light is irradiated to cause curing.

[0051] Next, an embodiment of the present invention in which at least one surface of the polarizing element has a urea-based compound-containing layer other than the adhesive layer containing at least one kind of urea-based compound will be described. As described above, the technical elements constituting the present invention, such as the [polarizing element] other than the [urea-based compound-containing layer], are common to the embodiment in which the urea-based compound-containing layer is an adhesive layer.

[0052] [Urea-based compound-containing layer] In this aspect of the present invention, the polarizing plate has a urea-based compound-containing layer (other than the adhesive layer) containing at least one compound selected from urea, urea derivatives, thiourea, and thiourea derivatives, formed on at least one surface of a polyvinyl alcohol-based resin polarizing element having iodine adsorbed and oriented thereon. The urea compound-containing layer preferably contains at least one urea compound and a binder. Examples of the binder include a polymer binder, a thermosetting binder, and an active energy ray-curable binder, and any of these binders can be preferably used in the present invention.

[0053] The thickness of the urea compound-containing layer is preferably from 0.1 to 20 μm, more preferably from 0.5 to 15 μm, and further preferably from 1 to 10 μm. The urea-based compound-containing layer may be laminated directly to the polarizing element or via another layer, but it is preferable to laminate it directly to the polarizing element in order to easily prevent a decrease in transmittance in a high-temperature environment. In this embodiment, the polarizing plate preferably has a transparent protective film on at least one surface of the polarizing element via an adhesive layer in order to increase the physical strength of the polarizing plate. In this case, the adhesive layer may or may not contain a urea-based compound, but it is more preferable that the adhesive layer contains a urea-based compound.

[0054] As described in the explanation of the protective film in other embodiments, in recent years, in order to meet the demand for thinner polarizing plates, polarizing plates having a protective film on only one side of the polarizing element (hereinafter also referred to as "polarizing plates with one-sided protective film") have been developed. In order to increase the physical strength of such a structure, attempts have been made to laminate a hardening layer on the surface of the polarizing element that does not have a protective film (for example, JP 2011-221185 A).

[0055] In the present invention, it is also one of the preferred aspects to include a urea-based compound in such a cured layer. Usually, such a cured layer is formed from a curable composition containing an organic solvent, but in paragraphs

[0020] to

[0042] of JP2017-075986A, a method of forming such a cured layer from an aqueous solution of an active energy ray curable polymer composition is described. Since many urea-based compounds are water-soluble, it is also one of the preferred aspects of the present invention to include a water-soluble urea-based compound in such a composition to form a urea-based compound-containing layer.

[0056] Next, a polarizing plate according to still another embodiment will be described, which has a polarizing element prepared by applying a solution containing a urea compound to at least one surface of the polarizing element and drying the applied solution. This embodiment is characterized in that the polarizing element is used in a polarizing plate for interlayer filling construction and prevents a decrease in single-unit transmittance even when exposed to a high-temperature environment for a long period of time. This polarizing element can be produced by coating at least one surface of a polarizing element made of a stretched polyvinyl alcohol-based resin film on which iodine is adsorbed and oriented, with a solution containing at least one selected from urea, urea derivatives, thiourea, and thiourea derivatives, and then drying the coating liquid.

[0057] (Urea compound solution) The solvent of the urea compound-containing solution of the present invention is preferably water, an organic solvent, or a mixture thereof, more preferably water or a mixed solvent of water and alcohol. In the case of a mixed solvent of water and alcohol, the alcohol is preferably either methanol or ethanol. As the urea compound, the above-mentioned urea compounds can be preferably used, but the urea compound is preferably water-soluble in order to prevent the urea compound from precipitating on the surface of the polarizing element after drying. EXAMPLES

[0058] The present invention will be specifically described below based on examples. The materials, reagents, amounts of substances and their ratios, operations, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the present invention is not limited to the following examples.

[0059] (Preparation of Polarizing Element 1) A 40μm thick PVA film with an average degree of polymerization of 2400 and a degree of saponification of 99.9 mol% was immersed in warm water at 25°C for 120 seconds to swell. The PVA film was then immersed in an aqueous solution of 0.6% by weight of iodine / potassium iodide (weight ratio = 2 / 3) and dyed while being stretched 2.1 times. The film was then stretched in an acid bath containing boric acid and potassium iodide at 60°C, washed with water, and dried to produce a polarizing element 1 with a thickness of 15μm.

[0060] (Preparation of PVA solution for adhesive) 50 g of modified PVA resin containing acetoacetyl groups (Mitsubishi Chemical Corporation: Gohsenex Z-410) was dissolved in 950 g of pure water, heated at 90° C. for 2 hours, and then cooled to room temperature to obtain a PVA solution for adhesive.

[0061] (Preparation of urea compound solution) 10 g of urea was added to 90 g of pure water to obtain a 10 wt % urea aqueous solution (Solution 1). Similarly, according to Table 1, solutions 2 to 9 were prepared by replacing urea with the urea-based compounds shown in Table 1 and, if necessary, changing the solvent from pure water to methanol.

[0062] [Table 1]

[0063] The urea, methylurea, ethylurea, 1,3-dimethylurea, tetramethylurea, phenylurea, thiourea, methylthiourea, and tetrahydro-2-pyrimidinone used above were all reagents manufactured by Tokyo Chemical Industry Co., Ltd.

[0064] (Preparation of Polarizing Plate Adhesive 1) The adhesive PVA solution, urea solution, pure water, and methanol prepared above were mixed to give a PVA concentration of 3.0%, a methanol concentration of 20%, and a urea concentration of 0.3%, to obtain an adhesive 1 for polarizing plates.

[0065] (Preparation of polarizing plate adhesives 2 to 14) Similarly, a PVA solution for adhesive, a solution of a urea-based compound shown in Table 1, pure water, and methanol were mixed to give a PVA concentration of 3.0%, a methanol concentration of 20%, and a urea-based compound concentration shown in Table 2, to obtain polarizing plate adhesives 2 to 14. The polarizing plate adhesive 12 uses two types of urea-based compounds, ie, methylurea and 1,3-dimethylurea, in combination, while the polarizing plate adhesive 14 does not contain a urea-based compound.

[0066] [Table 2]

[0067] (Saponification of Cellulose Acylate Film) A commercially available cellulose acylate film TD40 (manufactured by Fujifilm Corporation: film thickness 40 μm) was immersed in a 1.5 mol / L NaOH aqueous solution (saponification solution) kept at 55° C. for 2 minutes, then the film was washed with water, and then immersed in a 0.05 mol / L sulfuric acid aqueous solution at 25° C. for 30 seconds, and then passed through a water washing bath under running water for 30 seconds to neutralize the film. Then, the film was repeatedly drained three times with an air knife, and after removing the water, it was allowed to stay in a drying zone at 70° C. for 15 seconds and dried to produce a saponified film.

[0068] (Preparation of Polarizing Plate 1) The saponified cellulose acylate film prepared above was attached to both sides of the polarizing element 1 via polarizing plate adhesive 1, and the thickness of the adhesive layer after drying was adjusted to 100 nm on both sides. The films were then laminated using a roll laminator and dried at 60°C for 10 minutes to obtain polarizing plate 1 with cellulose acylate film on both sides.

[0069] (Preparation of polarizing plates 2 to 14) Polarizing plates 2 to 14 were produced in the same manner as polarizing plate 1, except that the adhesive 1 for polarizing plates was replaced with adhesives 2 to 14 for polarizing plates.

[0070] (Preparation of Laminate 1) With reference to the examples in JP 2018-025765 A, an acrylic adhesive (manufacturer: Lintec Corporation, product number: #7) was applied to both sides of the polarizing plate 1 prepared above to produce an optical laminate 1 having an adhesive layer 25 μm thick on both sides. (Preparation of Laminates 2 to 14) The optical laminate was prepared in the same manner as in the optical laminate 1, except that the polarizing plate 1 was replaced with polarizing plates 2 to 14. Layers 2 to 14 were produced.

[0071] (Preparation of Laminate 15) Optical laminate 15 was produced in the same manner as optical laminate 14, except that a pressure-sensitive adhesive layer was laminated on only one side of optical laminate 14.

[0072] (Evaluation of the laminate) The laminate prepared above was evaluated with reference to the examples in JP 2014-102353 A and JP 2018-025765 A. The high temperature durability test was performed at 95°C and 105°C, and the high temperature durability test was performed for up to 1000 hours at 95°C, but no decrease in transmittance was observed except for Comparative Example 1, which used polarizing plate adhesive 14 without the addition of a urea-based compound. Table 3 shows only the results of the high temperature durability test at 105°C. In the test results for Comparative Example 1, the coloring at 105°C for 100 hours was almost the same as the result at 95°C for 1000 hours.

[0073] [Evaluation of unit transmittance after high-temperature durability test (105℃)] The optical laminates 1 to 14 prepared above were each cut into a size of 50 mm x 100 mm, and the surfaces of the first adhesive layer and the second adhesive layer were each attached to alkali-free glass (trade name "EAGLE XG", manufactured by Corning Incorporated) to prepare evaluation samples. The optical laminate 15 was cut into a size of 50 mm x 100 mm, and the surface of the first adhesive layer was attached to non-alkali glass (trade name "EAGLE XG", manufactured by Corning Incorporated). In preparing these samples, no heat treatment for adjusting the moisture content was carried out before bonding to the glass plate. This evaluation sample was subjected to a temperature of 50°C and a pressure of 5kgf / cm 2 (490.3kPa) for 1 hour, and then left in an environment with a temperature of 23°C and a relative humidity of 55% for 24 hours. Thereafter, the transmittance was measured (initial value), and the sample was stored in a heated environment at a temperature of 105°C, with the transmittance measured every 50 hours from 100 to 200 hours. Evaluation was performed according to the following criteria, based on the time at which the transmittance had decreased by 5% or more from the initial value. The results are shown in Table 3. The evaluation sample including the optical laminate 15 had a structure in which the non-alkali glass was laminated only on one side, so the transmittance did not decrease and the evaluation result was A. The decrease in transmittance after 200 hours is 5% or less: A The transmittance drops by 5% or more after 150 to 200 hours: B The transmittance drops by 5% or more after 100 to 150 hours: C The transmittance drops by 5% or more after 100 hours: D

[0074] [Evaluation of cloth loss after high temperature durability test] The optical laminate 15 was cut into a size of 30 mm x 30 mm, and the surface of the first adhesive layer was attached to non-alkali glass (trade name "EAGLE XG", manufactured by Corning Incorporated) and cross-evaluated. Sample 20 was prepared for this purpose. The single transmittance evaluation sample after high temperature durability was evaluated 100 hours later, and then the optical laminate and sample 20 were visually inspected for light leakage in a cross-Nicol state (hereinafter simply referred to as "cross leakage") and evaluated according to the following criteria. No cross-drops are visible: ◎ Almost no cross-drops are visible: Slight cross-drop defects: △ Cross-drops are clearly visible: ×

[0075] [Table 3]

[0076] The amounts of urea compounds added in Table 3 will be explained below. As described above, the amount of the urea compound added to the adhesive is preferably 0.1 to 400 parts by weight, more preferably 1 to 200 parts by weight, and even more preferably 3 to 100 parts by weight, relative to 100 parts by weight of PVA. In this example, the PVA concentration is 3.0%. In the present invention, the greater the amount of any of the urea compounds added, the smaller the change in single unit transmittance after the high temperature durability test. Conversely, the smaller the amount of the compound added, the smaller the degree of cross loss after the high temperature durability test. All of the urea-based compounds described in the examples showed a change in single unit transmittance of B or higher after the high-temperature durability test, and at the same time showed an effect of △ or higher in cross loss, and thus exhibited excellent effects in both performances.

[0077] However, regarding the amount of the above compounds to be added, the range of the amount of addition that exhibits the preferred performance, i.e., the single-component transmittance change of B or more and the cross loss of △ or more, differs strictly depending on each compound, but the amount of addition of each compound is within the above-mentioned preferred amount range. The amounts added in Table 3 indicate the minimum amount added for each urea compound at which the single-unit transmittance is rated A. Furthermore, for urea and thiourea, the amounts added were gradually reduced from the minimum amount added for which the single-unit transmittance was rated A, and the amounts added are also shown at which the cross-passage changed from △ to ○ (the change in single-unit transmittance at this time was B). Furthermore, for methylurea, the amounts added were gradually reduced from the minimum amount added for which the single-unit transmittance was rated A, and the amounts added are also shown at which the cross-passage changed from ○ to ◎ (the change in single-unit transmittance at this time was B).

[0078] The results shown in Table 3 make the following clear: 1. The polarizing plate of the present invention, which uses an adhesive containing a urea-based compound, can suppress a decrease in single-unit transmittance even when used in an image display device with an interlayer filling configuration and when exposed to a high-temperature environment for a long period of time. 2. In particular, compared with the use of urea or thiourea, the use of urea derivatives or thiourea derivatives is particularly favorable since there is no decrease in the single-piece transmittance and no cross-drop. 3. The adhesive containing two types of urea-based compounds can also prevent the decrease in the single-piece transmittance even when exposed to a high-temperature environment for a long period of time, and is one of the preferred embodiments of the present invention.

[0079] Next, an example of another embodiment will be described, but this embodiment is also not limited to the following example. To the composition of the cured layer-forming composition BLC-1 described in paragraphs

[0075] to

[0076] of JP2017-075986A, methylurea was added so that the solid concentration of methylurea became 1 weight%, and pure water was added so that the total solid concentration became 26 weight%, and after mixing, the mixture was irradiated with ultrasound and passed through a filter with a pore size of 5 μm to prepare a urea compound-containing curable composition (UBLC-1).

[0080] With reference to polarizing plate 1 described in paragraphs

[0070] to

[0080] of JP2017-075986A, a polarizing plate (polarizing plate 22) having a cured layer and a one-sided protective film that does not contain a urea compound was produced. A polarizing plate (polarizing plate 21) having a one-sided protective film with a urea compound-containing cured layer was prepared in the same manner as polarizing plate 22, except that the cured forming composition (BLC-1) was replaced with the cured forming composition (UBLC-1). Optical laminates 21 and 22 were obtained in the same manner as optical laminate 14, except that polarizing plate 14 was replaced with polarizing plate 21 and polarizing plate 22, respectively. These samples were evaluated in the same manner as optical laminate 14, and the obtained results are shown in Table 4. The evaluation of the loss of cloth after high temperature durability was carried out with the transparent protective film surface facing outward.

[0081] [Table 4]

[0082] The results shown in Table 4 make clear the following: 1. The polarizing plate of the present invention, which has a urea-based compound-containing layer on at least one surface of a polarizing element, can suppress a decrease in single-unit transmittance even when used in an image display device with an interlayer filling configuration and even when exposed to a high-temperature environment for a long period of time.

[0083] Further, examples of other embodiments will be described below, but these embodiments are also not limited to the following examples. A 0.5% solution of methylurea was prepared as a coating solution. The 0.5% solution of methylurea was coated on one side of the polarizing element 1 prepared above using a bar coater so that the wet coating amount was 10 μm, and then dried at 60° C. for 5 minutes to obtain polarizing element 2. As a comparative example, pure water was applied to one surface of the polarizing element prepared above using a bar coater so that the wet coating amount was 10 μm, and then dried at 60° C. for 5 minutes to obtain polarizing element 3.

[0084] Polarizing plates 31 and 32 were obtained in the same manner as polarizing plate 14, except that polarizing element 1 was replaced with polarizing element 2 and polarizing element 3, respectively. Optical laminates 31 and 32 were obtained in the same manner as optical laminate 14, except that polarizing plate 14 was replaced with polarizing plate 31 and polarizing plate 32, respectively. These samples were evaluated in the same manner as optical laminate 14, and the results are shown in Table 5.

[0085] [Table 5]

[0086] The results shown in Table 5 make clear the following: 1. The polarizing plate of the present invention has a polarizing element prepared by applying a solution containing a urea-based compound to at least one surface of the polarizing element and drying the applied solution. Even when the polarizing plate is used in an image display device having an interlayer filling configuration, the decrease in the single-unit transmittance can be suppressed even when the polarizing plate is exposed to a high-temperature environment for a long period of time.

Claims

1. A polyvinyl alcohol-based resin polarizing element having iodine adsorbed thereon and oriented thereon; formed on at least one surface of the polarizing element A urea-based compound-containing layer containing at least one selected from urea, urea derivatives, thiourea, and thiourea derivatives; and Transparent Protective Film A polarizing plate comprising:

2. 2. The polarizing plate according to claim 1, wherein the urea compound-containing layer is an adhesive layer, and the transparent protective film is attached via the adhesive layer.

3. 3. The polarizing plate according to claim 2, wherein the adhesive layer further contains a polyvinyl alcohol resin.

4. 4. The polarizing plate according to claim 3, wherein the total content of the urea compounds contained in the adhesive layer is from 1 part by weight to 400 parts by weight based on 100 parts by weight of the polyvinyl alcohol resin.

5. 5. The polarizing plate according to claim 1, wherein the urea compound is a urea derivative and / or a thiourea derivative.

6. 6. The polarizing plate according to claim 2, wherein the adhesive layer has a thickness of 0.01 to 7 μm.

7. 2. The polarizing plate according to claim 1, wherein the urea compound-containing layer is a resin layer other than an adhesive layer.

8. 8. The polarizing plate according to claim 1, which is used in an image display device having an interlayer packing structure.

9. A method for producing a polarizing plate having a transparent protective film attached to at least one surface of a polarizing element, comprising the steps of: At least one surface of a polarizing element made of a stretched polyvinyl alcohol-based resin film on which iodine has been adsorbed and oriented is provided. Polyvinyl alcohol resin, and forming an adhesive layer using an adhesive composition containing at least one selected from urea, urea derivatives, thiourea, and thiourea derivatives; A method for producing a polarizing plate, comprising the step of laminating a transparent protective film via the adhesive layer simultaneously with or after the step of forming the adhesive layer.

10. An image display panel in which the polarizing plate according to any one of claims 1 to 8 is attached to a viewing side surface of an image display cell via a pressure-sensitive adhesive layer; and a transparent member attached to the viewing-side polarizing plate surface of the image display panel via an adhesive layer; An image display device comprising:

11. 11. The image display device according to claim 10, wherein the transparent member is a glass plate or a transparent resin plate.

12. The image display device according to claim 10, wherein the transparent member is a touch panel. Place.

Citation Information

Patent Citations

  • Liquid crystal panel support, electronic equipment having the same and manufacture of the same equipment

    JP1999174417A

  • Polarizing plate and image display device, and manufacturing method of those

    JP2014102353A